English Teachers’ Pedagogical Competence in Regard to Understanding the Students - G, Hasriani (Language Circle: Journal of Language and Literature, 2022)
This research aimed at identifying the English teachers’ pedagogical competence in understanding the students. The profile of English teachers’ pedagogical competence in understanding the students was based on the National Standard of Education, in section 28, sub-section 3 point a. The researcher employed descriptive evaluative method. The subjects of this research were four English teachers from different schools of Madrasah Aliyah in Kabupaten Enrekang. The purpose of the research was to describe the teachers’ pedagogical competence in understanding the students. Based on the result and discussion, the four teachers have different quality in terms of pedagogical competence especially in understanding the students. The score of teacher 1 and teacher 4 was 3 (good). They both could understand the students’ cognitive ability, whether the good or the poor students. They also paid attention to the different characteristics or ability of the students. Besides, they already paid attention to the students’ prior knowledge. They used to review the lesson in the previous meetings before coming to the next material. In another hand, the result showed that the score of teacher 2 and 3 was different from teacher 1 and teacher 4, that was 2 (poor). In understanding the students, teacher 2 and teacher 3 ignored one point, which is paying attention to the students’ prior knowledge. They never reviewed the last material before coming to the new material. Based on the result and discussion, it could be concluded that the four teachers had different quality in terms of pedagogical competence in regard to understanding the students. Since the teachers’ quality is the most important point in developing the students’ learning proficiency, the four English teachers still need more improvement. Because in Indonesia, the teachers who meet the standards of being professional teachers are the ones who have the required qualifications and truly understand what to do, whether inside or outside the classroom